Pursuing a corporate sustainable identity: Green governance strategy, hybrid vehicle development, knowledge and sustainability performance - Akrum Helfaya; Phuong Bui (Journal of Innovation & Knowledge (JIK), 2025)
The automobile industry's transition toward sustainability remains impeded by inconsistent green governance, which hampers progress in hybrid vehicle production. Existing literature predominantly focuses on technological innovation and consumer adoption, often overlooking the governance structures that foster environmental responsibility. This study proposes a framework of green governance strategy (GGS) designed to drive automakers' proactive engagement in hybrid vehicle development. Grounded in social identity theory, our research challenges traditional perspectives on green innovation within the automobile industry. It highlights that companies with robust GGS act as pivotal drivers of hybrid vehicle development. Contrary to prior studies that relegated green products to a peripheral status, our findings position hybrid vehicles as central to corporate identity, integrating environmental responsibility with long-term profitability and alignment with sustainable development goals (SDGs). The study further reveals that despite economic pressures such as rising electricity costs, companies committed to GGS continue to prioritize hybrid vehicle production as a critical strategy to enhance sustainability performance and secure recognition in sustainability awards. However, a significant gap persists: 60 % of surveyed companies fail to address SDG 11 (Sustainable Cities and Communities), while 55 % neglect SDG 13 (Climate Action). This misalignment emphasizes the need for more comprehensive goal integration across the sector. The findings provide valuable insights for scholars, policymakers, and industry standard-setters, offering guidance for developing future governance frameworks that support more holistic contributions to sustainable urban and climate goals.
Keywords: M41; L62; L90; 650; Green governance strategy; Hybrid vehicle development; Environmental performance; Sustainable development; Social identity theory